Kontruksi Citra Muslim Moderat dalam Film Religi Indonesia: Analisis Naratif Pesan Dakwah - Cindy Aulia Putri; Diah Rahmaniar; Muhammad Saleh; Nadiyatul Rahimah Sinaga (STIKes Ibnu Sina Ajibarang, 2025)
The aim of this research is to see how moderate Muslim culture is depicted in Indonesian religious films by looking at da'wah. Religious films are one of the most effective media for conveying Islamic values ​​to the general public and examining relevant social and ideological dynamics. This research uses narrative analysis as part of a qualitative approach to find features, preaching messages and story elements. The main focus is how religious films help people better understand Islam by encouraging tolerance, inclusion and relevance to modern society. This study found that Indonesian religious films often depict social and spiritual conflicts that prevent Muslims from maintaining moderate values. People who encourage conversation, defend moral principles, and reconcile religious education with contemporary life are representative of moderate Muslims. It is hoped that this research will be a guide for filmmakers who want to make films that depict Islam in a moderate way.